Cold Tolerance in Two Large Maize Inbred Panels Adapted to European Climates. Issue 5 (1st September 2014) - Revilla, Pedro; Rodríguez, Víctor Manuel; Ordás, Amando; Rincent, Renaud; Charcosset, Alain; Giauffret, Catherine; Melchinger, Albrecht E.; Schön, Chris‐Carolin; Bauer, Eva; Altmann, Thomas; Brunel, Dominique; Moreno‐González, Jesús; et al.
ABSTRACT: Maize ( Zea mays L.) for northern growing areas requires cold tolerance for extending the vegetative period. Our objectives were to evaluate two large panels of maize inbred lines adapted to Europe for cold tolerance and to estimate the effects of cold‐related traits on biomass production. Two inbred panels were evaluated for cold tolerance per se and in testcrosses under cold and control conditions in a growth chamber and under field conditions. Comparisons of inbreds and groups of inbreds were made taking into account the single nucleotide polymorphisms (SNP)‐based genetic structure of the panels, and the factors affecting biomass production were studied. Eight flint and one dent inbred with diverse origins were the most cold tolerant. The most cold‐tolerant dent and flint groups were the Iodent Ph207 and the Northern Flint D171 groups, respectively. The relationships between inbred per se and testcross performance and between controlled and field conditions were low. Regressions with dry matter yield in the field as dependent variable identified plant height ( R 2 = 0.285) as the main independent variable, followed by quantum efficiency of photosystem II ( R 2 = 0.034) and other traits with minor contributions. Cold‐tolerance–related traits had low and negative effects on dry matter yield. Models intending the prediction of final performance from traits scored in early developmental stages are not expected to be precise enough for breeding. For improving cold tolerance, inbreds released from crosses among the No Iodent group and the Northern Flint group may show high combining ability, as well as between both groups and the Northern Flint D171 group.